Growth, Yield and Fatty Acid Profile of Winged Bean (Psophocarpus tetragonolobus) Seeds with Shoot Pruning and Additional Fertilizer - Tustiyani, Isna; Melati, Maya; Aziz, Sandra Arifin; Syukur, Muhamad; Faridah, Didah Nur (Universitas Sebelas Maret, 2023)
Winged bean is a remarkable climbing plant, distinguished by its multiple segments that serve as growth sites for shoot, leaf and flower. Several studies have shown that the plant requires shoot pruning to increase the production of its flower buds, pods and seeds, but this practice can inhibit the generative phase. To overcome this challenge, the application of additional fertilizer is needed to provide the required nutrients. Therefore, this study aims to determine the effects of shoot pruning and additional fertilizer on the growth, yield and bioactive compounds of winged bean seeds. The determination of the proper rates of fertilization was important for plant production and to support sustainable agriculture. The study procedures were carried out at IPB experimental station in Leuwikopo, IPB University, Bogor. A Randomized complete block design (RCBD) was utilized with two factors and three replications, namely leaf pruning (without shoot pruning, 15 cm, and 30 cm from the ground) and additional fertilizer (0, 6.25, 12.5 and 18.5 g NPK 16-16-16 plant-1). The parameters observed included plant height, leaf nutrient, root length, yield, leaf number, as well as protein and fatty acid profile of seeds. The results showed that shoot pruning treatment and additional fertilizer had no interaction effect on plant growth and seed yield. Shoot pruning caused an increase in leaf number, fatty acid and linoleic acid content by 17% to 20%, 10%, and 16% to 19%, respectively, compared to the control. The use of additional fertilizer at a concentration of 6.25 to 12.5 g NPK (16-16-16) plant-1 increased leaf number, nutrients, and seed yield. Based on the findings, the highest seed yield (2.56 tons ha-1) was achieved with the application of additional fertilizer at the rates of 6.25 g NPK (16-16-16) plant-1, but shoot pruning was not required.